2019
DOI: 10.1016/j.omtn.2019.07.023
|View full text |Cite
|
Sign up to set email alerts
|

circFBXW7 Inhibits Malignant Progression by Sponging miR-197-3p and Encoding a 185-aa Protein in Triple-Negative Breast Cancer

Abstract: Accumulating evidence indicates that circular RNAs (circR-NAs) are vital regulators of various biological functions involved in the progression of multiple cancers. Circular F-box and WD repeat domain containing 7 (circFBXW7) (hsa_circ_0001451) has been reported to act as a tumor suppressor by encoding a novel protein in glioma; however, its functions and mechanisms in triple-negative breast cancer (TNBC) remain elusive. In the current study, we validated by qRT-PCR that circFBXW7 was downregulated in TNBC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
178
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(184 citation statements)
references
References 48 publications
5
178
0
1
Order By: Relevance
“…As expected, the interaction between miR-197-3p and TUSc8 was confirmed by luciferase reporter and RIP assays. According to previous studies, miR-197-3p plays an oncogenic role in breast cancer, bladder cancer and thyroid cancer (19,20,42,43). However, the anti-oncogenic role of miR-197-3p has been found in prostate cancer and gastric cancer (44,45).…”
Section: Discussionmentioning
confidence: 98%
“…As expected, the interaction between miR-197-3p and TUSc8 was confirmed by luciferase reporter and RIP assays. According to previous studies, miR-197-3p plays an oncogenic role in breast cancer, bladder cancer and thyroid cancer (19,20,42,43). However, the anti-oncogenic role of miR-197-3p has been found in prostate cancer and gastric cancer (44,45).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, circRNA can also act as a tumor suppressor in the development and progression of cancer. For example, circFBXW7 inhibits tumor growth and metastasis in glioma and breast cancer by encoding a 21kDa novel protein FBXW7-185aa and blocking miR-197-3p Ye et al, 2019). circMTO1 suppresses malignancy progression by serving as the sponge of oncogenic miR-9 to upregulate p21 expression in human hepatocellular carcinoma (Han et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It interacts competitively with the deubiquitinating enzyme USP28, which antagonizing USP28-induced c-Myc stabilization. Another recent work demonstrated that FBXW7-185aa can inhibit the proliferation and migration of triple-negative breast cancer cells by increasing the abundance of FBXW7 and inducing c-Myc degradation [103].…”
Section: Translation Of Circfbxw7 In Glioma and Breast Cancermentioning
confidence: 99%